Sex Trafficking Victims at Their Junction with the Healthcare Setting—A Mixed-Methods Inquiry. Issue 1 (1st January 2020) - Richie-Zavaleta, Arduizur Carli; Villanueva, Augusta; Martinez-Donate, Ana; Turchi, Renee M.; Ataiants, Janna; Rhodes, Shea M.
ABSTRACT: U.S.-born citizens are victims of human trafficking typically exploited through sex trafficking. At least some of them interact with healthcare providers during their trafficking experience; yet a majority goes unidentified. Although protocols and training guides exist, healthcare providers often do not have the necessary skills to identify and assist victims of sex trafficking. Understanding where victims seek care and barriers for disclosure are critical components for intervention. Thus, this study interviewed survivors of sex trafficking to ascertain: a) healthcare settings visited during trafficking, b) reasons for seeking care, and c) barriers to disclosing victimization. An exploratory concurrent mixed-methods approach was utilized. Data were collected between 2016–2017 in San Diego, CA and Philadelphia, PA (N = 21). Key findings: 1) Among healthcare settings, emergency departments (76.2%) and community clinics (71.4%) were the most frequently visited; 2) medical care was sought mainly for treatment of STIs (81%); and 3) main barriers inhibiting disclosure of victimization included feeling ashamed (84%) and a lack of inquiry into the trafficking status from healthcare providers (76.9%). Healthcare settings provide an opportunity to identify victims of sex trafficking, but interventions that are trauma-informed and victim-centered are essential. These may include training providers, ensuring privacy, and a compassionate-care approach.